Bis{1-[3-(diethylammonio)propyliminomethyl]naphthalen-2-olato}nickel(II) dinitrate - Xiao-Hui Ji; Jiu-Fu Lu (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, [Ni(C18H24N2O)2](NO3)2, consists of one half of the centrosymmetric nickel(II) complex cation and a nitrate anion. The NiII atom, lying on an inversion center, is four-coordinated by the phenolate O atoms and imine N atoms of two Schiff base ligands, forming a square-planar geometry. The O- and N-donor atoms are mutually trans. In the crystal structure, the nitrate anions are linked to the complex cations by intermolecular N—H...O hydrogen bonds.